Social and Ecological Potential of Spaces for Public and Free Use of Buildings in the Municipality of Paranaguá-Paraná - Souza, Letícia Yasmin Silva de; Tonetti, Emerson Luis; Valaski, Simone (Technical and Scientific Journal Green Cities, 2021)
The squares are spaces for public use and free from buildings that can help the population in terms of improving urban environmental quality and quality of life. In an urban segment of the municipality of Paranaguá, this research aimed to quantify and qualify the existing infrastructure to infer the social and ecological potential of each square. 29 squares were selected in the central area of the municipality of Paranaguá, on the coast of Paraná. In these, the presence and quality of equipment for use by the population was observed; ground cover materials and tree canopy cover, taking into account the potential for reducing heat islands and water infiltration into the ground. The data collected in the field were compiled into a general framework for analysis and later transcribed to graphics, for interpretation of the social and ecological potential. Of the total number of squares, only 2 had low social and ecological potential. The results also showed the presence of diverse infrastructure with a predominance of squares that are more used for rest and contemplation. Based on the classes of materials that formed the existing ground cover and the percentage of vegetation cover, it can be pointed out that the ecological potential of the squares can be expanded. Therefore, the possibility of implementing changes in the squares of the urban segment of Paranaguá to improve the social and ecological potential to meet the needs of the citizens must be considered. KEYWORDS: Square. Social potential. Ecological potential.